1990
DOI: 10.3181/00379727-195-43150
|View full text |Cite
|
Sign up to set email alerts
|

Peptides of Myelin Basic Protein Are Encephalitogenic in Rats without the Aid of Emulsions

Abstract: Immunization with peptides is usually done with the aid of Freund's adjuvant. Using peptides derived from myelin basic protein, we show that aqueous solutions can be antigenic (encephalitogenic in this instance) in Lewis rats. The first procedure involved multiple doses of aqueous peptide, increased absorption into the lymphatic system from the peritoneal cavity in the postinflammatory state, and the use of pertussis vaccine. Three different peptides containing the major encephalitogenic site were active in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Increased absorption of antigen into the lymph nodes is likely to increase the immune response. Recently, it has been found that absorption of antigens and other materials from the peritoneal cavity of rats is increased during the healing (postinflammatory) phase of a chemical peritonitis [1][2][3][4], Subsequent enhancement of the immune response has been found in studies of hemagglutinating antibodies [5] and several forms of cellmediated immunity: graft-vs.-host disease and hostvs.-graft response [2], experimental allergic encepha lomyelitis and adrenalitis [2,[6][7][8][9][10], and adjuvant arthritis [11]. In the present work, enhancement of sys temic anaphylaxis has been produced by sensitizing or challenging rats in the postinflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Increased absorption of antigen into the lymph nodes is likely to increase the immune response. Recently, it has been found that absorption of antigens and other materials from the peritoneal cavity of rats is increased during the healing (postinflammatory) phase of a chemical peritonitis [1][2][3][4], Subsequent enhancement of the immune response has been found in studies of hemagglutinating antibodies [5] and several forms of cellmediated immunity: graft-vs.-host disease and hostvs.-graft response [2], experimental allergic encepha lomyelitis and adrenalitis [2,[6][7][8][9][10], and adjuvant arthritis [11]. In the present work, enhancement of sys temic anaphylaxis has been produced by sensitizing or challenging rats in the postinflammatory state.…”
Section: Introductionmentioning
confidence: 99%